(untitled) (Research, Society and Development, 2023)
Objective: To identify, in the available literature, nursing care for pregnant women with syphilis in Primary Care. Methodology: This is an integrative literature review study, developed in six stages of methodological profiles. Thus, the PICo strategy was used, a strategy related to a non-clinical method. Results: The sample of this research concludes in 07 studies that will be developed throughout the article, focusing on clear and explanatory points. Discussion: In view of the above, the study points out that the lack of knowledge of the interviewees may be related to the evolution of the diseases and other injuries, since it is extremely necessary to have the parameters of assistance conducts for the growth of knowledge and to better understand the coping that the patient it’s passing. Conclusion: This work allowed the immensity of knowledge, in view of the scientific analyzes presented and how it is necessary, the learning of the pregnant woman and her partner in relation to syphilis and in the evolution of the promotion, prevention, treatment and assistance of the nurse being essential, since their role is fundamental for such behaviors and results.